2020
DOI: 10.5194/hess-24-5973-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir evaporation in a Mediterranean climate: comparing direct methods in Alqueva Reservoir, Portugal

Abstract: Abstract. Alqueva Reservoir is one of the largest artificial lakes in Europe and is a strategic water storage for public supply, irrigation, and energy generation. The reservoir is integrated within the Multipurpose Alqueva Project (MAP), which includes almost 70 reservoirs in a water-scarce region of Portugal. The MAP contributes to sustainability in southern Portugal and has an important impact on the entire country. Evaporation is the key component of water loss from the reservoirs included in the MAP. Evap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…This indicates significant impacts of all meteorological factors on EP. Similar results were also reported from different climatic regions of the world (Hounguè et al, 2019;Rodrigues et al, 2020). The present study also found that all meteorological variables are required for reliable estimation of EP.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates significant impacts of all meteorological factors on EP. Similar results were also reported from different climatic regions of the world (Hounguè et al, 2019;Rodrigues et al, 2020). The present study also found that all meteorological variables are required for reliable estimation of EP.…”
Section: Discussionsupporting
confidence: 91%
“…This situation is in contrast with the substantial water loss associated with irrigation, in agriculture (Boulet et al, 2020), to which snowmaking is often compared (Steiger et al, 2019). Water storage for agriculture is often questioned, in particular due to the fact that strong evaporation from the reservoirs can occur, leading to direct loss of stored water (Rodrigues et al, 2020), and that water used for irrigation is lost through the evapotranspiration of the agricultural plants and soils. Due to colder temperature prevailing at the location where water reservoirs used for snowmaking are built, it is likely that the evaporation rate from such reservoirs is much smaller than from lower elevation agricultural reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…The Alqueva reservoir-the biggest artificial lake in southern Europe (area ≈ 250 km 2 ) -is in the Beja and Évora districts (southern Portugal) (Figure 1Al) and is within the municipalities of Portel and Moura. It is integrated within the Multipurpose Alqueva Project (MAP), which includes almost 70 reservoirs in this water-scarce region of the country [43]. This reservoir is inserted in the Guadiana hydrographic basin, following the waterline of the Guadiana River.…”
Section: In Situ Datamentioning
confidence: 99%
“…The surrounding landscape is composed of non-irrigated arable lands, permanently irrigated land, fruit trees and berry plantations, olive groves, complex cultivation patterns, agro-forestry areas, broad-leaved forest, and coniferous forest [45]. The climate of this region is classified as a Csa Region according to the Köppen climate classification, which corresponds to a Mediterranean climate (i.e., a temperate climate with dry, hot summers) [43,46].…”
Section: In Situ Datamentioning
confidence: 99%